The Effectiveness of Learning to Write Procedure Text in Pjbl Model with Poster Media Based on Collaborative Competency of Grade Xi Islamic Senior High School Students - Mansyur, Muhammad; Zulaeha, Ida; Yuniawan, Tommi (Universitas Negeri Semarang, 2022)
The educational needs of students need to be adapted to the needs of the local and global environment in the era of society 5.0. The application of 21st century competency content, especially collaboration, can make students able to compete, think critically, creatively, and innovatively in solving problems. This research aims to determine the effectiveness of learning writing procedural text skills in a project-based model with poster media based on collaborative competence in grade XI Madrasah Aliyah students. This type of research is an experimental design with a non-equivalent control group design. The purpose of this study was to determine the difference between students' initial abilities and the state after treatment. The result of the research is that there are significant differences in the process and learning outcomes of the PjBL model in the ability to write procedural texts with poster media based on collaborative competence in grade XI Madrasah Aliyah students. Poster media is effectively used in learning to write procedural texts based on the collaboration competence of grade XI Madrasah Aliyah students. This is evidenced by the students' pre-test and post-test learning outcomes. The pre-test data of experimental class students' learning outcomes showed an average of 66.00 while the post test results were 85.00 so there was a difference of 19.00. The results of the paired sample t-test on the poster media showed that student learning outcomes had a Sig value. (2-tailed) 0.000 <0.05 while the t-count value is 15.855 > the t-table value is 1.688. In addition, the results of the assessment of student attitudes during the learning process showed a value of 87.57%. The benefit of research is that it provides a choice of teaching models and media for teachers and students to help students understand procedural texts.